Notes on Early Land Plants Today. 34. Validation of Scapania gaochii (Scapaniaceae, Marchantiophyta) - Cao, Tong; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2013)
Scapania gaochii was described from Yunnan without indication of the herbarium where the type was conserved. Therefore, this name was invalidly published (ICN Art. 37.7; McNeill et al. 2012) and needs validation. The format of this note follows Söderström et al. (2012) except that we use the Melbourne International Code of Nomenclature for algae, fungi, and plants (ICN; McNeill et al. 2012) instead of the Vienna International Botanical Code of Nomenclature (ICBN; McNeill et al. 2006).